Profit Taxation and Bank Risk Taking - Michael Kogler (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
How can tax policy improve financial stability? Recent studies point to large potential stability gains from a reform that eliminates the debt bias in corporate taxation. Such a reform reduces bank leverage. This paper emphasizes a novel, complementary channel: bank risk taking. We model the portfolio choice of banks under moral hazard and thereby highlight the 'incentive function' of equity. The corporate income tax influences risk-taking incentives through the cost of equity relative to deposits, the after-tax returns on different portfolios, and future bank profits. The analysis yields two novel findings: A tax reform which eliminates the debt bias discourages risk taking and reduces bank failure risk. Raising the corporate tax rate can also reduce risk taking in the short run, but permanent tax hikes have destabilizing long-term effects.
Keywords: G21; G28; H25; 330; Corporate taxation; tax reform; risk taking; financial stability